Structural and Functional Studies of the Thromboxane A2 Receptor for Rational Drug Design - Krawinski, Pawel (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2024)
The thromboxane A2 receptor (TP) is a G protein-coupled receptor (GPCR) that belongs to the prostanoid subfamily of class A GPCRs. TP plays critical roles in cardiovascular function as it leads to platelet aggregation and smooth muscle contraction once activated by its highly unstable endogenous ligand, thromboxane A2 (TxA2). This receptor is implicated in a number of thrombotic disorders and cardiovascular diseases such as myocardial ischemia, heart failure, and myocardial infarction. Given its important physiological and pathophysiological roles, TP is an attractive therapeutic target. As part of this thesis, two high-resolution single-particle cryogenic electron microscopy (cryo- EM) structures of active TP were solved in complex with stable mimetics of TxA2, U46619 and I-BOP, as well as the mini-Gq heterotrimeric G protein, to 3.26 Å and 3.25 Å resolution, respectively. The structures revealed the molecular details of agonist interactions with TP binding pocket residues, and unveiled a unique activation mechanism, driven by Q3017.46 in TM7 of the receptor. Additionally, insights into the movement of TM1, a characteristic feature of TP during activation, have been provided. The TP structures should help in the rational design of much needed new TP drugs. The findings of all TP studies were supported by extensive mutagenesis and computational experiments. Furthermore, exploratory work was conducted with a TP-BRIL construct suitable for use in the structure determination of the inactive state of the receptor. Preliminary experiments have shown successful complex formation between TP-BRIL and the anti-BRIL antibody, BAG2, for fiducial-assisted cryo-EM. Future work on this construct should result in the elucidation of inactive state TP structures in complex with clinically relevant antagonists, such as NTP42, which are currently undergoing development for treating conditions like pulmonary arterial hypertension and other cardiopulmonary disorders, where TP plays a significant role. Moreover, molecular docking and molecular dynamics simulations were performed with several TP antagonists, which have shown a common binding mechanism, which could be exploited for more efficient drug design, as well as their potential route of entry into the receptor’s binding pocket. Lastly, as part of this thesis, the thermotropic and lyotropic mesophase behaviour of a novel monoacylglyceride (MAG), 7.10 MAG, was characterized through the construction of temperature-composition phase diagrams using small-angle X-ray scattering. The suitability of this novel MAG as a host lipid for the in meso crystallization of GPCRs was tested using a model GPCR, the adenosine A2A receptor. An X-ray crystal structure of the receptor, using crystals grown in 7.10 MAG, was solved to 2.4 Å resolution, substantiating the use of this lipid for structure determination of GPCRs by the in meso method.
APPROVED
Keywords: Thromboxane A2 receptor; G protein-coupled receptors; Rational drug design; Cryo-EM structure determination; Crystal structure determination; Molecular dynamics simulations; Molecular docking